A New Model of Body Composition: Concept and Design Features of the DBA-Model - Dahlmann, Nicolaus (Journal of Obesity Management, 2026)
Indices, based on data such as height and weight in general and in particularly the body mass index (BMI), are often used to assess overweight. However, there is limited capacity to differentiate the amount of fat mass between individuals. This review refers to an anthropometric model called Dahlmann-Body-Analysis (DBA), which uses simple anthropometric parameters to define a Reference Weight (Ref-Wt). It is based on hand circumference as a proxy for the skeletal frame and, in addition, the circumference of the abdomen as a proxy for central obesity. Processed through a network of algorithms, the DBA model enabled to differentiate the Difference Weight – that means the difference between the Actual Weight and the Reference Weight – into fat mass and skeletal muscle mass. The DBA-model resembles the 2-component model of Albert R. Behnke, which he considered as a living functional construct including essential fat. The DBA-model matches with Behnke`s 2-component model insofar, as the essential fat is replaced by a physiological amount of fat tissue. The review summarizes studies to compare DBA-derived data with Metropolitan Life Insurance tables, evaluates DBA-derived fat tissue mass with bioelectrical impedance analysis (BIA) derived results and analyses the meaning of the DBA model in clinical settings to uncover the underlying mechanisms of metabolic syndrome (MetS) pathogenesis with increasing amounts of fat mass. The model offers the opportunity to calculate changes in fat or muscle tissue in an absolute (kg) or relative (%) amount on individuals. The data suggest that the DBA-model has satisfactory prediction qualities for use as a practical tool in public health care.
Keywords: Dahlmann-Body-Analysis (DBA); body composition; fat tissue; muscle mass; obesity; sarcopenia; aging